2020
DOI: 10.2340/16501977-2749
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum to Fear of movement in patients attending cardiac rehabilitation: A validation study

Abstract: The authors have unfortunately discovered that the originally published version of this article contains errors, due to the incorrect merging of two datasets. These errors lead to minor changes of the paper, but need to be corrected.In this corrigendum, we supply the corrected data in Table I and also updated abstract, results and discussion sections. These corrections do not alter the study's findings of significance or overall interpretation of the study results. The authors regret for any inconvenience caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…In a previous study, a similar result was found. 1 Moreover, we found that kinesiophobia mediated the relationship between cardiac anxiety and CR initiation. This finding is in line with previous research which reports that kinesiophobia mediates the relationship between self-rated anxiety and CR attendance.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…In a previous study, a similar result was found. 1 Moreover, we found that kinesiophobia mediated the relationship between cardiac anxiety and CR initiation. This finding is in line with previous research which reports that kinesiophobia mediates the relationship between self-rated anxiety and CR attendance.…”
Section: Discussionmentioning
confidence: 70%
“…Scores on the TSK-NL Heart are categorised as follows: subclinical: 13–22; mild: 23–32; moderate: 33–42 and severe: 43–52. 1 After 3 months, patients were asked, by telephone, if they (1) were referred for CR, (2) initiated CR, (3) were readmitted to the hospital for an unplanned procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are limited data regarding fear of movement in patients with CVD, who tend to have a high level of kinesiophobia, probably based on the anxiety and inability to cope with fear of exercising, which that may trigger their symptoms – mostly angina, resulting in an avoidance of activity or movement. In 2 studies, the level of kinesiophobia was reported to be high among 45.5% and 20% of the study populations, including cardiac patients [ 11 , 12 ]. Elevated levels of kinesiophobia and fear avoidance belief to PA were also detected in patients with coronary artery disease (CAD) and rheumatic heart disease [ 13 ].…”
Section: Introductionmentioning
confidence: 99%